Pemanfaatan Tes Inteligensi dalam Asesmen Psikologi Klinis: Memahami Gangguan Kepribadian Skizotipal - Toto, Kezia Charissa; Poerwandari, Elizabeth Kristi (Universitas Airlangga, 2024)
This case report aims to illustrate the use of an Indonesian intelligence test for adults, TIDI, in clinical assessment, particularly in understanding cognitive dysfunctions in schizotypal personality disorder. This case involved a college student who commit sexual verbal violence on campus. Following observation, interviews, and initial assessments, a diagnostic impression of schizotypal personality disorder was established, prompting the administration of TIDI to explore participant’s cognitive function. Cognitive dysfunctions exhibited by the participant include circumstantial thinking and speech, inability to inhibit subjective responses, difficulty focusing on important aspects of stimuli, eccentric preference for symmetry, poor social adaptation skills, and limited ability for problem-solving. Analysis with Dual Process Theory showed that the participant was more likely to depend on Type 1 processing, which relies on intuitive reasoning and prior knowledge. The implications highlight the benefits of using TIDI in psychological assessments to gain a comprehensive understanding of personality disorders.